Ex Libris Andrzeja piwowarczyka [!] [Andrzej Piwowarczyk]. - Piwowarczyk, Andrzej (1919-1994) (1958)
W czerwonej ramce fotografia rzeźby Augusta Rodina "Myśliciel", pod nią napis: Ex Libris Andrzeja piwowarczyka.